A Latent Transition Analysis of Perceived Parental Security Profiles Across 33 Months of Adolescence. Issue 2 (13th December 2019) - Andretta, James R.; Morgan, Grant B.; Wells, Kevin E.; McKay, Michael T.
Abstract : Objective: To examine associations among perceived parental security (PPS) profiles—that is, perceived communication quality with one's parents as well as feelings of trust and alienation toward them—and outcomes across 33 months of adolescence. Background: Using cross‐sectional data, researchers have developed PPS profiles by categorizing adolescents based on Inventory of Parent and Peer Attachment—Revised (IPPA–R) scores. Researchers have not examined the stability of PPS profiles during adolescence. Method: PPS among early adolescents ( N = 2, 032; M age = 12.5; female = 50%) was assessed using IPPA–R scores, and profiles were identified using latent profile analysis. A mover–stayer, latent transition analysis was used to examine the degree to which moving between or staying within a particular PPS profile was associated with five outcomes—emotional, social, and academic self‐efficacy, sensation seeking, and subjective life expectancy—in this developmental period. Results: At both data collections, profiles were not strongly associated with sex. Low‐Security profiles were disproportionately represented by individuals eligible for a free school lunch. Transitions to, or remaining in, the Low‐Security profile between Wave 1 and Wave 2 were generally associated with unfavorable outcomes. Conclusion: PPS profiles and transitions accounted for a parent bond construct that was strongly associated with meaningful outcomes. Therefore, person‐centered analyses of IPPA–R scores, such as latent profile and transition analyses, are preferred methods of accounting for PPS in adolescence. Implications: IPPA–R might be a useful tool for counselors working with adolescents, because scores point to tangible targets for intervention: (a) feelings of alienation from parents, (b) quality of communication with parents, and (c) feeling trusted by parents.